Moving beyond the exclusionary politics of migration: a response from the Social Sciences - Wylie, Gillian (Biblical interpretation, 2018)
This paper offers a response from the social sciences to the papers in this special edition. Drawing on the disciplines of Peace Studies and International Relations, three key themes emerge from these papers on migration stories in the Bible which resonate with the politics and responses now playing out in the current European ‘migration crisis’. These themes are (1) the exclusionary politics driving much migration policy; (2) the importance of acknowledging the agency of migrants; and (3) hints of what alternative responses to migration might look like. This paper draws out the presence of these themes across the collection and relates them to the current situation. Ultimately, while the papers reveal an interminable tendency to ‘other’ the migrant, they also sew the seeds of ideas about alternative approaches to migration which listen to migrant voices and build diverse communities.